Electrochemical deposition of lithium coating on titanium implant with enhanced early stage osseointegration. Issue 11 (23rd May 2022) - Huang, Tingben; Yu, Zhou; Yu, Qiong; Chen, Yitong; Jiang, Zhiwei; Wang, Ying; Yang, Guoli
Abstract: Recently, a large number of studies have reported that lithium (Li) displayed a positive effect on osteogenesis. However, only a few studies have investigated the Li‐incorporated surfaces through electrochemical deposition. In this study, electrochemical deposition was conducted on a CHI600E electrochemical workstation. The characterization of electrochemical deposition (ECD) and ECD‐Li surfaces were detected by field‐emission scanning electron microscopy with energy‐dispersive spectrometer. rBMSCs were cultured on two surfaces for subsequent adhesion, proliferation and live/dead assay. To evaluate the effects of Li‐incorporated implants by electrochemical deposition on osseointegration in vivo, teeth extraction of two premolars and one first molar in bilateral mandible were performed on six male beagle dogs. After 3 months, ZDI and ZDI‐Li implants were inserted into the bilateral mandible of each beagle dog. Micro Computed Tomography (Micro‐CT) and hard tissue sectioning analysis were carried out to evaluate the osseointegration at 4‐ and 8‐weeks post‐implantation. Results showed that ECD‐Li surface promoted adhesion and proliferation of BMSCs in the early stage. More importantly, through micro‐CT analysis, the values of bone volume/total volume (BV/TV) (0.374 ± 0.015), bone‐implant contact (BIC) (0.831 ± 0.025), and Tb.Th (0.412 ± 0.007) in ZDI‐Li group was significantly higher than those of ZDI group (0.302 ± 0.009, 0.700 ± 0.023, 0.353 ± 0.001, p < .01) at 4 weeks. Similarly, ZDI‐Li group manifested more bone contact with the implant surfaces at 4 weeks based on hard tissue sectioning analysis, whereas no significant difference was detected between two groups at 8 weeks. Therefore, incorporating Li into implant surface through ECD could enhance early osseointegration in vivo.